One health’s “Jurassic Park moment”: tempered reasons for optimism - Jonathan Beever; Nicolae Morar (Global Bioethics)
In this short analysis, we argue that while One Health approaches have remained anthropocentric (i.e. morally and practically prioritizing human health), One Health is due for its “Jurassic Park moment.” Such a moment would mark a shift in moral priority, balancing human interests against nonhuman interests. Examples of theory and practice in One Health support the potential for such a shift.